What is the healthcare carbon footprint? A collaborative analysis of current literature. (30th September 2020) - Di Fonzo, D; Rivolta, S; Mazzolai, E; Turatto, F; Mammana, L; Righini, M
Abstract: Background: Climate change (CC) is a public health (PH) issue of growing concern. Health care systems in every country have a significant impact in terms of greenhouse gas emissions (GHGE) causing global warming, but there seems to be a general lack of knowledge about this. As members of the junior study group on CC and PH of the Italian Society of Hygiene (SItI), we launched a project of shared education and literature research about the carbon footprint of healthcare (HCCF). We believe such an effort to be useful in spreading awareness and promoting change both in clinical practice, health care management and at policymaking level. Objectives: To answer these questions: What is the estimated national and global HCCF? Which activities contribute to HCCF? What are the possible actions and policies to reduce HCCF while providing universal health care of good quality in all countries? From Dec 2019 to Feb 2020 we used databases and backward citation searching to retrieve references which we split among individuals to process, then we shared summaries of the material with the group. Results: HCCF makes about 4.4% of all GHGE, with important variations among countries. We found estimates on emissions for various activities (e.g. operating theatres) and items (e.g. inhalers), as well as proposed solutions for practitioners, managers, manufacturers and policymakers (e.g. low-impact technologies, advocacy, health promotion to reduce healthcare volumes). Conclusions: HCCF is complex, attributable to many components and amenable to mitigation through actions at all levels, with additional benefits for efficiency and public health. These conclusions are relevant for all countries as they imply joint international and transversal efforts throughout the world's health care sector. Key messages: Current data and analysis, available for several services and in many countries, show healthcare carbon footprint is significant. Emissions from health sector can be reduced while granting universal healthcare globally.